Karakterisasi Nano Ziolit Teraktifasi ZnCl 1 dan Aplikasinya pada Limbah Cair Pabrik Minyak Kelapa Sawit - Deddi Midwar; Syaifullah Muhammad; Muhammad Faisal; Ida Hasmita (Fakultas Teknik, 2018)
The industrial liquid waste is very dangerous because it still contains elements of pollutants with a relatively large waste parameters. One way that can be used is by the method of adsorption or absorption. In this research the absorbent used is Natural Zeolite in nano meter scale. Zeolitewith nano meter size is obtained by smoothing using ball mill for 15 - 20 hours. Furthermore, nano zeoliteis activated physically and chemically. Nano zeolite will be characterized using X-ray Diffraction (XRD), Fourier Transform Infarared (FTIR), Scanning Electron Microscopy (SEM), and characterization of N adsorption desorption. Results of the study obtained the highest adsorption capacity and percent removal is performed by ziolites that are activated with nano-size ZnCl2 with a value of 440.5 mg/g for adsorption capacity and 65.9% for percent removal. In this study, the equation for calculating the zeolite performance in lowering the COD content in the effluent was used Langmuir’s isotherm equation. The determinant coefficient (R22) of the Langmuir isotherm equation for 35 μm zeolite and non-activated nano meter performance were 0.9974 and 0.9983, respectively. While unzaked zeolitefor size 35μm and nano meter are respectively equal to 0,9977 and 0,9197.